A Construção e as Artes ao tempo de D. Sesnando: Parte 2: Coimbra e Montemor no século XI - Real, Manuel Luís; Fernandes, Paulo Almeida (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2021)
D. Sesnando’s rule over a vast territory, between the rivers Mondego and Douro (1064-1091), entailed a rupture with the previous framework of territorial management, in which a considerable part of this land was nominally bound to Muslim authorities. After the definitive conquest of Coimbra, there was a period of intense change in the landscape and of enhancement of humanized geography, in which the alvazil Sesnando moved more intensely. This article seeks to address the reality of construction and the arts during D. Sesnando’s time. Based on documental sources that mention various types of heritage, the first part of the paper offered an analysis of the territory. It also included an introduction to the city of Coimbra, between the Muslim invasion of 711 and the eve of the 1064 conquest. In addition we present an overview of the performance of the dux Sesnando.